Painting Walls with Imagination - Samia Singh (Black Book)
Samia Singh is an artist and designer whose artworks overcome conventional language and communication barriers across contexts. Working across mediums, her art is rooted in themes that exhalt the natural landscape. She has had work commissioned in municipalities of Italy, Spain and in Japan. Wherever and whatever she has worked on, she leaves a spirited mark of the timelessness of natural beauty and its related feeling of joy regardless of place. Her works are broadly categorizable as fantasy-laden images and site-specific nature-scapes often inspired by the surrounding landscape and seemingly by her childhood growing up in Punjab.